2012
DOI: 10.1103/physreve.86.041918
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and length distribution of microtubules under force and confinement

Abstract: We investigate the microtubule polymerization dynamics with catastrophe and rescue events for three different confinement scenarios, which mimic typical cellular environments: (i) The microtubule is confined by rigid and fixed walls, (ii) it grows under constant force, and (iii) it grows against an elastic obstacle with a linearly increasing force. We use realistic catastrophe models and analyze the microtubule dynamics, the resulting microtubule length distributions, and force generation by stochastic and mea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 47 publications
1
49
0
Order By: Relevance
“…Improved mean-field results including this effect [28] agree quantitatively with full stochastic simulations [see Fig. 5(a) and 5(c)].…”
Section: Stochastic Fluctuationssupporting
confidence: 73%
See 1 more Smart Citation
“…Improved mean-field results including this effect [28] agree quantitatively with full stochastic simulations [see Fig. 5(a) and 5(c)].…”
Section: Stochastic Fluctuationssupporting
confidence: 73%
“…Finally, we want to note that the collective dynamics for N ≫ 1 that we described here differ markedly from the dynamics of a single MT (N = 1) [7]. For a single MT rescue does not happen at a particular force level F min but after an average time 1/ω r set by the individual rescue rate.…”
Section: Limit Cycle Oscillations and Absence Of Bifurcationsmentioning
confidence: 77%
“…The negative effects of polymerization force, when generated against a rigid barrier, on the growth velocity of microtubules was first shown experimentally by Dogterom and Yurke [29] and subsequently studied theoretically by other authors(see, e.g., [30][31][32][33]). Experiments have also shown that the catastrophe frequency is enhanced by the proximity of the microtubule tip to a barrier, both in vitro [28] and in vivo [34], which is consistent with a reduced binding rate in the presence of force (see [35,36], two recent theoretical studies of h ow microtubule dynamic instability is affected by force and confinement). Interestingly, the 13-protofilament model used by the authors of [30,31,33] is similar to the model studied in the second part of this paper.…”
Section: Discussionmentioning
confidence: 62%
“…Another model proposes that oscillations occur via a general mechanobiochemical feedback (25). Models of force-dependent MTs interacting with the same object also exhibit cooperative behavior (5,(26)(27)(28)(29). However, these models do not explain error correction dynamics.…”
mentioning
confidence: 99%